Food addiction as a mediator in the association between depression and body mass index among young adults in South Korea: a cross-sectional study - Hyegyeong Cha; Seunghye Yun; Bokyoung Kim (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study examined the relationships among olfactory function, depression, food addiction, and body mass index (BMI) and assessed whether food addiction mediated the associations of olfactory function and depression with BMI among young Korean adults. Methods: This cross-sectional descriptive study included 158 adults recruited from a university campus in Cheonan, South Korea (mean age, 25.10 years). Olfactory function, depressive symptoms, and food addiction were assessed using the YSK olfactory function test, Patient Health Questionnaire-9, and Yale Food Addiction Scale 2.0, respectively; BMI was measured using bioelectrical impedance analysis. Data were analyzed using SPSS version 24.0 and the PROCESS macro version 4.2. Results: Current smoking status (β = .22, p = .006), depression (β = −.20, p = .024), and food addiction (β = .18, p = .044) were significantly associated with BMI. Food addiction significantly mediated the association between depression and BMI (B = 0.07, 95% bias-corrected bootstrap confidence interval: 0.01–0.15) but not the association between olfactory function and BMI. Depression had a positive indirect association with BMI through food addiction, whereas its direct association with BMI was negative, indicating an inconsistent mediation, or suppression, pattern. Conclusion: Food addiction mediated the relationship between depression and BMI in this sample. Depression was associated with higher BMI through addictive-like eating rather than through its direct pathway. Healthcare providers may consider screening for addictive-like eating behaviors as a modifiable target for obesity prevention among young adults with depressive symptoms.